2021
DOI: 10.3390/life11070594
|View full text |Cite
|
Sign up to set email alerts
|

Description of a CSF-Enriched miRNA Panel for the Study of Neurological Diseases

Abstract: Background: The study of circulating miRNAs in CSF has gained tremendous attention during the last years, as these molecules might be promising candidates to be used as biomarkers and provide new insights into the disease pathology of neurological disorders. Objective: The main aim of this study was to describe an OpenArray panel of CSF-enriched miRNAs to offer a suitable tool to identify and characterize new molecular signatures in different neurological diseases. Methods: Two hundred and fifteen human miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…An analysis of cerebrospinal fluid from 215 healthy subjects showed high levels of miR-204-5p in normal brain and spinal cord tissues, and the authors speculated that diseases in brain and spinal cord tissues may directly lead to the abnormal expression of miR-204-5p. 16 In the present study, it was found that miR-204-5p expression was down-regulated in the CCI rat model, and intrathecal injection of miR-204-5p lentivirus not only increased the concentration of miR-204-5p in the spinal cord but also improved the thresholds of mechanical and thermal pain stimulation in rats. This result was consistent with the down-regulation of miR-204-5p in the SCC model described by Shen et al 12 …”
Section: Discussionsupporting
confidence: 48%
“…An analysis of cerebrospinal fluid from 215 healthy subjects showed high levels of miR-204-5p in normal brain and spinal cord tissues, and the authors speculated that diseases in brain and spinal cord tissues may directly lead to the abnormal expression of miR-204-5p. 16 In the present study, it was found that miR-204-5p expression was down-regulated in the CCI rat model, and intrathecal injection of miR-204-5p lentivirus not only increased the concentration of miR-204-5p in the spinal cord but also improved the thresholds of mechanical and thermal pain stimulation in rats. This result was consistent with the down-regulation of miR-204-5p in the SCC model described by Shen et al 12 …”
Section: Discussionsupporting
confidence: 48%
“…CSF samples were run in triplicate using custom-configured OpenArray plates (cc-OA) specially designed to analyze CSF-enriched miRNAs. 18 miRNA cDNA templates were diluted to 1:20 in tris-EDTA buffer and combined with the same volume of TaqMan OpenArray Real-Time PCR Master Mix. After loading the samples into the OpenArray plate, qPCR was performed using a QuantStudio 12K Flex Real-Time PCR System (Applied Biosystems, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Serum miRNA expression values were normalized using the mean value of 2 endogenous miRNAs (miR-15a-5p and miR-23a-3p), whereas CSF expression values were normalized using the mean value of 8 endogenous miRNAs (miR-16 + miR-24 + miR-125a + miR-30d + miR-26b + miR-145 + miR-92b + miR-23a), as shown in a previous search of suitable endogenous normalizers in these CSF samples. 18 The delta cycle threshold method was also used to calculate the relative expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another study suggested that the disruption of DGCR8-dependent microRNA biogenesis is crucial for the 22q11.21 copy number variant (CNV) genes involved in psychiatric disorders for late fetal cortical development [9]. MiRNomics has also been analyzed by some authors who described a panel of CSF-enriched miRNAs as a possible tool to identify and characterize new molecular signatures in different neurological diseases [10].…”
mentioning
confidence: 99%